Calculated studies for the braking efficiency of freight trains under the rules of gost 34434-2018 with the application of universal formulas (four-axle gondola cars, covered railraod cars, platforms, dump cars) (Transport systems and technologies, 2020)
Absence of normative values of the actual coefficients in new rules of GOST 34434-2018 does not allow implementing and determining the optimal characteristics of the brake according to the previously adopted conditions of braking efficiency (braking distance), which causes uncertainty in solving this problem. The uncertainty lies in the fact that the choice of the characteristics of the brake system of a freight car has to be carried out by enumerating a large number of variations. In this respect, the article provides tools for determining the actual coefficient of the press force of composite brake blocks on  wheels, satisfying the given braking efficiency of the freight train. Universal formulas are used as tools in the form of power dependence between the actual coefficient of press force of brake blocks and the braking distance of a freight train. The coefficients of universal formulas are obtained on the basis of computer simulation. Numerous examples show that the error in the use of universal formulas in calculation studies does not exceed 0.5% compared to the calculated ones according to GOST 34434-2018 methodology. Values of actual coefficients are given depending on the axial load of the car and speed at which the braking distances of the freight train correspond to the standard minimum permissible values. It is shown that performance of the calculation studies using universal formulas in the EXCEL environment allows automate the calculation process in full. A technique is proposed for determining the gear ratio of the brake lever mechanism of a freight car, at which a given braking efficiency is performed. The proposed technique allows you to perform multivariate studies on the selection of optimal parameters of the brake system of freight cars that meet the specified requirements for braking efficiency, and greatly facilitates the calculation studies.
Keywords: Actual coefficient, braking distance, speed, axial load, power dependence, coefficients, gear ratio